Sex‐based differences in antiretroviral therapy initiation, switching and treatment interruptions: global overview from the International Epidemiologic Databases to Evaluate AIDS (IeDEA). Issue 6 (29th June 2018) - Giles, Michelle L; Achhra, Amit C; Abraham, Alison G; Haas, Andreas D; Gill, Michael John; Lee, Man Po; Luque, Marco; McGowan, Catherine; Cornell, Morna; Braitstein, Paula; de Rekeneire, Nathalie; Becquet, Renaud; et al.
Abstract: Introduction: In 2015, the World Health Organization recommended that all HIV‐infected individuals consider ART initiation as soon as possible after diagnosis. Sex differences in choice of initial ART regimen, indications for switching, time to switching and choice of second‐line regimens have not been well described. The aims of this study were to describe first‐line ART and CD4 count at ART initiation by sex, calendar year and region, and to analyse time to change or interruption in first‐line ART, according to sex in each region. Methods: Participating cohorts included: Southern, East and West Africa (IeDEA‐Africa), North America (NA‐ACCORD), Caribbean, Central/South America (CCASAnet) and Asia‐Pacific including Australia (IeDEA Asia‐Pacific). The primary outcomes analysed for each region and according to sex were choice of initial ART, time to switching and time to discontinuation of the first‐line regimen. Results and Discussion: The combined cohort data set comprised of 715, 252 participants across seven regions from low‐ to high‐income settings. The median CD4 count at treatment initiation was lower in men compared with women in nearly all regions and time periods. Women from North America and Southern Africa were more likely to switch ART compared to men ( p < 0.001) with approximately 90% of women reporting a major change after 10 years in North America. Overall, after 8 years on ART, >50% of HIV‐ positive men and women from Southern Africa, East Africa, South and Central America remained on their original regimen. Men were more likely to have a treatment interruption compared with women in low‐ and middle‐income countries from the Asia/Pacific region ( p < 0.001) as were men from Southern Africa ( p < 0.001). Greater than 75% of men and women did not report a treatment interruption after 10 years on ART from all regions except North America and Southern Africa. Conclusions: There are regional variations in the ART regimen commenced at baseline and rates of major change and treatment interruption according to sex. Some of this is likely to reflect changes in local and international antiretroviral guideline recommendations but other sex‐specific factors such as pregnancy may contribute to these differences.